Laureano Gómez, la Misión Currie y el proyecto de reforma constitucional de1952 - Malagón Pinzón, Miguel (2023)
This article seeks to outline the structure, justifications and proposal of the Currie Mission and Laureano Gómez’s attempt to amend the constitution during his government. T his study is very important for the history of constitutional law in Colombia in the first half of the twentieth century. This paper analyzes forgotten sources and concludes that Gómez tried to impose a strange mixture of American and European right wing i deas in Colombia.